2017
DOI: 10.1002/2016ef000486
|View full text |Cite
|
Sign up to set email alerts
|

Geoengineering, marine microalgae, and climate stabilization in the 21st century

Abstract: Society has set ambitious targets for stabilizing mean global temperature. To attain these targets, it will have to reduce CO 2 emissions to near zero by mid-century and subsequently remove CO 2 from the atmosphere during the latter half of the century. There is a recognized need to develop technologies for CO 2 removal; however, attempts to develop direct air-capture systems have faced both energetic and financial constraints. Recently, BioEnergy with Carbon Capture and Storage (BECCS) has emerged as a leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 36 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…Given that seawater is one of the more sustainable water sources for cultivation [135], and that only 23% of the total 518 treatments in this meta-analysis grew marine algae, more marine algae stains should also be tested in recycled medium. Here, marine algae were associated with lower mean ES C and ES µ than freshwater algae, though the results are not significant( Figure S13).…”
Section: Recommended Areas For Future Researchmentioning
confidence: 99%
“…Given that seawater is one of the more sustainable water sources for cultivation [135], and that only 23% of the total 518 treatments in this meta-analysis grew marine algae, more marine algae stains should also be tested in recycled medium. Here, marine algae were associated with lower mean ES C and ES µ than freshwater algae, though the results are not significant( Figure S13).…”
Section: Recommended Areas For Future Researchmentioning
confidence: 99%
“…In order to have positive effects on CO 2 bio-mitigation, it is necessary to improve the power requirement in the cultivation stage [2]. In this sense, the cultivation of marine microalgae in outdoor systems involves a greater reduction of the energy requirements and would allow the upscaling of the cultivation of microalgae biofuels [9,14].…”
Section: Climate Actionmentioning
confidence: 99%
“…The existing literature and life cycle assessments (LCAs) have shown contradictory results, which complicate the understanding of the feasibility of the process [2,12,13]. However, there is a consensus to deeply explore the real possibilities, especially for marine microalgae in coastal areas [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the IPCC suggested that in addition to many low/zero emissions technologies (e.g., solar, wind, and nuclear power, fossil energy with carbon capture and storage [CCS], carbon neutral crops, etc.) net‐negative‐emissions technologies are needed to limit temperatures to less than 2°C above preindustrial conditions (Fuss et al, ; Greene et al, , ; IPCC, ; Walsh et al, ). Net‐negative‐emissions technologies include bioenergy with CCS (BECCS), afforestation, direct capture of carbon dioxide (DAC) from the air, and other carbon dioxide removal technologies.…”
Section: Introductionmentioning
confidence: 99%